2014
DOI: 10.3109/07357907.2014.909826
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 was Highly Expressed in Human Primary Hepatocellular Carcinoma and Promoted Tumor Progression

Abstract: B7-H3 has been detected in different cancers and correlated to tumor progression and outcome in cancer patients. In this study, we investigated the expression of B7-H3 in tissues and cells of primary hepatocellular carcinoma (PHC) patients. The research showed that B7-H3 is aberrantly expressed in PHC tissues and cells, and its high expression on HepG2 cells significantly promotes cell proliferation, adhesion, migration, and invasion capacity; moreover, it inhibits the proliferation of CD8(+) T cells. Thus, B7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…Although our previous findings (10) revealed an association between tumor tissue B7-H3 levels and clinicopathological characteristics, the present study identified no significant association between sB7-H3 levels and certain clinicopathological characteristics, including age, sex and lymph node metastasis. However, sB7-H3 levels were found to differ significantly among the clinical stages examined, and were associated with distant metastasis.…”
Section: Association Between Sb7-h3 Il-17 Il-8 and Il-6 Levels In Hcontrasting
confidence: 99%
See 3 more Smart Citations
“…Although our previous findings (10) revealed an association between tumor tissue B7-H3 levels and clinicopathological characteristics, the present study identified no significant association between sB7-H3 levels and certain clinicopathological characteristics, including age, sex and lymph node metastasis. However, sB7-H3 levels were found to differ significantly among the clinical stages examined, and were associated with distant metastasis.…”
Section: Association Between Sb7-h3 Il-17 Il-8 and Il-6 Levels In Hcontrasting
confidence: 99%
“…However, neither of these are highly specific markers for liver cancer (27), and therefore, the attention of numerous researchers has turned toward finding a more specific diagnostic marker for liver cancer. Previously, we reported that B7-H3 levels were increased in the tumor tissue of HCC patients (10). In the present study, this investigation was extended to include serum levels of sB7-H3 and the cytokines IL-17, IL-8 and IL-6 in HCC patients, and the potential of combining these factors for use as diagnostic biomarkers of HCC was evaluated.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The precise functions of CD276 in tumor immunity are complicated as both T cell co-stimulatory and co-inhibitory effects have been reported [13]. Recently, emerging studies reveal that high tumor CD276 expression is correlated with more advanced disease and poor prognosis [9, 14, 15]. And CD276 also affects tumor progression and chemosensitivity by regulating oncogenic signaling pathways activated in non-immunological systems [16, 17].…”
Section: Introductionmentioning
confidence: 99%